The Effect of Gadget Use on Emotional Development in Early Childhood: A Health Education Approach - Siti Robi’atus Sholiha; Mery Angreani Safitri; Mufidatul Jariyah (Jurnal Ar Ro'is Mandalika (Armada), 2026)
The use of gadgets has become a part of modern family life and is increasingly observed among young children, including in residential areas like Woodville Residence Sidoarjo. Children’s dependence on digital devices is a concern, as it may hinder their emotional development. This study aims to describe how gadget use impacts the emotional development of young children and assess parents’ understanding of the associated risks. The research employs a descriptive approach with a survey method targeting parents of children aged 3–6 years. Data were collected through a structured questionnaire that includes the duration of gadget use, parenting patterns, and indicators of the child’s emotional development. The results show that the majority of children use gadgets beyond the recommended limits, and this condition correlates with signs of emotional instability, such as irritability, low self-confidence, and difficulty in controlling emotions. These findings emphasize that the role of parents in regulating gadget use is crucial to ensure optimal emotional development in children.